Dictionaries as sources of folklore data - Hopkin, D (Universitat Rovira i Virgili, 2021)
Roper, Jonathan (ed.): Dictionaries as Sources of Folklore Data. Folklore Fellows Communications 321. Helsinki: Academia Scientiarum Fennica, 2020, 246 p.